Automated treatment planning of prostate stereotactic body radiotherapy with focal boosting on a fast‐rotating O‐ring linac: Plan quality comparison with C‐arm linacs. Issue 9 (28th July 2021) - De Roover, Robin; Crijns, Wouter; Poels, Kenneth; Dewit, Bertrand; Draulans, Cédric; Haustermans, Karin; Depuydt, Tom
Abstract: Purpose: The integration of auto‐segmentation and automated treatment planning methods on a fast‐rotating O‐ring linac may improve the time efficiency of online adaptive radiotherapy workflows. This study investigates whether automated treatment planning of prostate SBRT with focal boosting on the O‐ring linac could generate plans that are of similar quality as those obtained through manual planning on clinical C‐arm linacs. Methods: For 20 men with prostate cancer, reference treatment plans were generated on a TrueBeam STx C‐arm linac with HD120 MLC and a TrueBeam C‐arm linac with Millennium 120 MLC using 6 MV flattened dual arc VMAT. Manual planning on the Halcyon fast‐rotating O‐ring linac was performed using 6 MV FFF dual arc VMAT (HA2‐DL10) and triple arc VMAT (HA3‐DL10) to investigate the performance of the dual‐layer MLC system. Automated planning was performed for triple arc VMAT on the Halcyon linac (ET3‐DL10) using the automated planning algorithms of Ethos Treatment Planning. The prescribed dose was 35 Gy to the prostate and 30 Gy to the seminal vesicles in five fractions. The iso‐toxic focal boost to the intraprostatic tumor nodule(s) was aimed to receive up to 50 Gy. Plan deliverability was verified using portal image dosimetry measurements. Results: Compared to the C‐arm linacs, ET3‐DL10 shows increased seminal vesicles PTV coverage (D99% ) and reduced high‐dose spillage to the bladder (V37Gy ) and urethra (D0.035cc ) but this came at the cost of increased high‐dose spillage to the rectum (V38Gy ) and a higher intermediate dose spillage (D2cm). No statistically significant differences were found when benchmarking HA2‐DL10 and HA3‐DL10 with the C‐arm linacs. All plans passed the patient‐specific QA tolerance limit. Conclusions: Automated planning of prostate SBRT with focal boosting on the fast‐rotating O‐ring linac is feasible and achieves similar plan quality as those obtained on clinical C‐arm linacs using manual planning.